2019
DOI: 10.1186/s13046-018-1018-6
|View full text |Cite
|
Sign up to set email alerts
|

Very low intensity ultrasounds as a new strategy to improve selective delivery of nanoparticles-complexes in cancer cells

Abstract: BackgroundThe possibility to combine Low Intensity UltraSound (LIUS) and Nanoparticles (NP) could represent a promising strategy for drugs delivery in tumors difficult to treat overcoming resistance to therapies. On one side the NP can carry drugs that specifically target the tumors on the other the LIUS can facilitate and direct the delivery to the tumor cells. In this study, we investigated whether Very Low Intensity UltraSound (VLIUS), at intensities lower than 120 mW/cm2, might constitute a novel strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
233
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(241 citation statements)
references
References 49 publications
4
233
0
Order By: Relevance
“…Cesi et al showed that a novel truncated form of ALK can be shuttled by vemurafenib resistant melanoma cell-derived exosomes and promote resistance phenotype in recipient cells [ 77 ]. Moreover, exosome-mediated transfer of p-STAT3 from resistant cells significantly promoted cell survival and 5-FU resistance both in vitro and in vivo [ 78 ].…”
Section: Role Of Exosomes In Dysregulation Of Oncogenes or Tumor Suppmentioning
confidence: 99%
“…Cesi et al showed that a novel truncated form of ALK can be shuttled by vemurafenib resistant melanoma cell-derived exosomes and promote resistance phenotype in recipient cells [ 77 ]. Moreover, exosome-mediated transfer of p-STAT3 from resistant cells significantly promoted cell survival and 5-FU resistance both in vitro and in vivo [ 78 ].…”
Section: Role Of Exosomes In Dysregulation Of Oncogenes or Tumor Suppmentioning
confidence: 99%
“…Another study showed that adipocytes induced CD36 expression in ovarian cancer cells, which promoted metastasis of cancer cells in peritoneum and omentum [ 147 ]. And also, CD36 was shown to be a key mediator of fatty acids-induced metastasis of gastric cancer cells via the AKT/glycogen synthase kinase (GSK)-3β/β-catenin signaling pathway [ 148 ].…”
Section: Metabolic Reprogramming To Form Metastatic Tumorsmentioning
confidence: 99%
“… 111 Models of the tumor immune microenvironment have also been developed to better understand cancer-immune interactions, in order to enhance immunotherapy efficacy. 112 The biophysical properties of these complex models have been effectively characterized using microrheology.…”
Section: Novel Biomaterials Designed Through Microrheologymentioning
confidence: 99%